Implementasi Peraturan Daerah Kabupaten Bungo Nomor 6 Tahun 2015 tentang Pengelolaan Sampah di Kelurahan Tanjung Gedang Kecamatan Pasar Muara Bungo - Ataka Rama Reta; Ikhsan Alfarisi; Joko Susanto (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2020)
Estimated solid waste generated in Bungo District in a day is about 143 tons, and the leading sector in waste management in Bungo Regency is the Office of the Environment, identifying problems in implementing Bungo District Regulation No. 6/2015 on Waste Management in Tanjung Gedang Village, among others: Lack Temporary Shelter, low participation and awareness of the community in maintaining cleanliness, lack of socialization from the government to the community towards the Regional Regulation. The purpose of this study is to examine in depth related to the implementation and inhibiting factors in the implementation of the Regional Regulation in Tanjung Gedang Village. The method used in this research is descriptive method with a qualitative approach. The informants in this study numbered twelve people who were determined by purposive sampling and accidental sampling techniques. The results of this study note that the implementation of Waste Management in Tanjung Gedang Urban Village has not been implemented in accordance with the established regulations, it can be seen from the implementation of rights, obligations, prohibitions, waste management, and sanctions that have not been implemented in accordance with the rules has been established. The inhibiting factors in the implementation of the Regional Regulation are: there is no location and geographically Tanjung Gedang Village is near the riverbanks, making it difficult to create a Temporary Shelter, and there is no waste handling activity. Lack of adequate waste management facilities causes low participation and public awareness in maintaining environmental cleanliness. The limited budget causes a lack of socialization of the Regional Regulation to the public, and there is no firm action from the Government on the enforcement of the norms that have been regulated therein.